Mutant p53—a potential player in shaping the tumor–stroma crosstalk - Stein, Yan (J Mol Cell Biol, 2019)
A plethora of studies suggest that the non-transformed cellular and non-cellular components of the tumor, collectively known as the tumor microenvironment, have a significant impact on the tumorigenic process. It was suggested that the microenvironment, which initially restricts tumor development, is recruited by the tumor and maintains a crosstalk that further promotes cancer progression. Indeed, many of the molecules that participate in the tumor–stroma crosstalk have been characterized. However, the crucial factors that are responsible for the initiation of this crosstalk or the ‘recruitment’ process remain poorly understood. We propose that oncogenes themselves may influence the ‘recruitment’ of the stromal cells, while focusing on mutant p53. Apart from losing its tumor-suppressing properties, mutant p53 gains novel oncogenic functions, a phenomenon dubbed mutant p53 gain of function (GOF). Here, we discuss possible ways in which mutant p53 may modulate the microenvironment in order to promote tumorigenesis. We thus propose that mutant p53 may serve as a key player in the modulation of the tumor–stroma crosstalk in a way that benefits the tumor. Further elucidation of these ‘recruitment’ processes, dictated by mutant p53, may be utilized for tailoring personalized therapeutic approaches for patients with tumors that harbor p53 mutation.